Meningkatkan Hasil Belajar Gerak Dasar Lokomotor Melalui Pendekatan Tematik Integratif Pada Siswa Kelas IV SD Kristen Mesa Kecamatan TNS Kabupaten Maluku Tengah - Krisantono, Rendy; Latar, Idris Moh (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2025)
The purpose of this study was to determine the extent to which locomotor basic movements can be improved through an integrative thematic approach conducted through class action research.. The research was conducted in 2 cycles. The object of this research this research is the learning outcomes of locomotor and integrative thematic approach.. This research was conducted at SD Kristen Mesa, TNS Sub-district, Central Maluku Regency.Central Maluku Regency. The subjects in the study were fourth grade students of SD Kristen Mesa, totalling 24 students which totalled 24 people. Which consisting of 12 boys, and 12 girls. The time location used takes place within 1 (one) month starting from November 10 to December 10, 2022 Data were analysed using descriptive statistics. the results of the study obtained percentage completeness learning outcomes in cycle I 41.67% (10 people) with an average score of 69.71% and there was an increase in the percentage of learning outcomes in cycle II. people) with an average score of 69.71% and an increase of 9.45% to 100%. an increase of 9.45% to 100% (20 people) in cycle II with an average score of 79.71%. reached 79.71%. Based on the results of data analysis and discussion, it can be concluded that the learning outcomes of locomotor basic movements increased through an integrative thematic approach in students class IV of Mesa Christian Elementary School, TNS District, Central Maluku Regency.